(untitled) (Global Journal of Science Frontier Research, 2023)
The devolution of power and resources by the State to local authorities much en vogue today in Cameroon and other areas of the world is fast becoming a governance model which could be relied upon for the assertion and articulation of communities based land management and ownership rights. This is so given that the advantages of bringing local communities to the decision-making centres to determine the fate of local lands and resource ownership and control can hardly be exhaustive in any single legal debate. Besides, it might be key to determining communities’ rights, while enhancing the dignity of its members. After all, communities’ lands are not only owned by a single generation, but by those considered as ancestors, the living and those yet to be born. To this effect, an attempt to weave the pieces of national land legislations within the decentralization paradigm arguably remains ideal in articulating efficient land governance.